Prompt gamma-ray analysis of Antarctic meteorites (1) – C1-related chondrites - Ebihara, Mitsuru; Shirai, Naoki; Yamaguchi, Akira; Osawa, Takahito (2023)
The 14th Symposium on Polar Science/Ordinary sessions [OA] Antarctic Meteorite, Tue. 14 Nov. / 3F Multipurpose Conference room, Institute of Statistical Mathematics conference object